Aspergillusidone G Exerts Anti-Neuroinflammatory Effects via Inhibiting MMP9 Through Integrated Bioinformatics and Experimental Analysis: Implications for Parkinson’s Disease Intervention - Fangfang Ban; Longjian Zhou; Zhiyou Yang; Yayue Liu; Yi Zhang (Marine Drugs)
Natural products have extensive attractiveness as therapeutic agents due to their low toxicity and high efficiency. Our previous study has identified a depside-type Aspergillusidone G (Asp G) derived from Aspergillus unguis DLEP2008001, which shows excellent neuroprotective activity for 1-methyl-4-phenylpyridinium (MPP+)-induced primary cortical neurons and anti-neuroinflammatory property, promising to be a potential therapeutic agent for Parkinson’s disease (PD). To further explore the anti-PD potential and mechanisms of Asp G, we employed network pharmacology, cellular experiments, and various biological techniques for analysis and validation. The analysis of network pharmacology suggested that Asp G’s anti-PD potential might be attributed to its modulation of inflammation. The data from nitric oxide (NO) detection, qRT-PCR, and Western blot confirmed that Asp G dose-dependently inhibited lipopolysaccharide (LPS)-stimulated NO production, with 40 μM Asp G suppressing 90.54% of the NO burst compared to the LPS group, and suppressed the overproduction of inflammatory-related factors in LPS-induced BV2 cells. Further protein–protein interaction analysis indicated that matrix metalloproteinase 9 (MMP9), a promising target for PD intervention, was the most likely anti-PD target of Asp G, and the results of gelatin zymography, qRT-PCR, and Western blot validated that Asp G could inhibit the active and inactive forms of MMP9 directly and indirectly, respectively. Notably, the inhibition of 67 kDa-MMP9 by Asp G is expected to compensate for the inability of TIMP-1 to inhibit this form. Furthermore, a selective inhibitor of MMP9 (20 μM SB-3CT) further potentiated the anti-inflammatory effects of Asp G (20 μM), with inhibition rate on NO increasing from 27.57% to 63.50% compared to LPS group. In summary, our study revealed that Asp G exerts anti-neuroinflammatory effects by inhibiting MMP9, which provides a valuable lead compound for the development of anti-neuroinflammatory drugs and offers insights into the intervention of PD-associated neuroinflammation. Future studies will further investigate the upstream regulatory mechanisms of Asp G-mediated MMP9 inhibition and its effects in in vivo PD models.